Occurrence of Zearalenols (Diastereomeric Mixture) in Corn Stalk Rot and Their Production by Associated Fusarium Species - Bottalico, Antonio (1985)
Zearalenol was extracted from Fusarium-infected stems of corn from southern Italy. The toxin, which appeared as a single compound in various thin-layer chromatography systems, was resolved by high-pressure liquid chromatography into two components. A gas chromatography-mass spectrometry examination of a purified fraction confirmed the natural occurrence of zearalenol as a diastereomeric mixture and led to the identification of alpha (56 ng/g) and beta (27 ng/g) isomers. Among nine Fusarium species found associated with stalk rot in corn, only Fusarium culmorum (F. roseum `Culmorum') and F. equiseti (F. roseum `Gibbosum') produced zearalenol and always produced it in a diastereomeric mixture of alpha and beta isomers.